Stabilitas Harga Dinamika Ekonomi: Hubungan antara Suku Bunga dan Volume Uang Tersebar terhadap Inflasi Indonesia 2022-2024 - Kautsar, Azkia Zahra; Rindiani, Dini; Humaira, Nayla Hasna; Nur Adha, Imelda Febrianty; Prawiraputri, Raden Tasya Nurhaliza; Maesaroh, Syti Sarah (Pusat Riset dan Inovasi Nasional, 2025)
Abstract. Inflation is an economic phenomenon characterized by an unrelenting surge in the prices of commodities and services over a defined period. When this price surge occurs repeatedly and is supported by high levels, the situation is categorized as inflation. One of the consequences of inflation is a decrease in people's purchasing power. During the 2022–2024 period, Indonesia experienced considerable price instability. This research aims to empirically investigate how BI's interest rates and the total money in circulation affect the inflation rate. The testing was conducted using a statistical assumption approach and hypothesis testing. The research findings indicate that Bank Indonesia's interest rate policy has a substantial impact on controlling the inflation rate in Indonesia. Keywords: Inflation Rate, BI Interest Rate, Money Supply